6 Evaluation of the Effect of Farrowing Pen Width on Piglet Pre-Weaning Mortality. (10th April 2018) - Harper, H M; Vande Pol, K D; Laudwig, A L; Ellis, M; Gaines, A M; Peterson, B A; Shull, C M
Abstract: Recent increases in litter size on commercial swine units have been associated with increases in pre-weaning mortality. Increasing farrowing pen width may be an approach to reducing pre-weaning mortality in larger litters. The objective of this study was to evaluate the effects of farrowing pen width on pre-weaning piglet mortality. This study was carried out at a commercial breed-to-wean facility using a RCBD with 2 farrowing pen width treatments: Standard (1.52 m; 0.48 m on both sides of sow crate); Increased (1.68 m; 0.48 m on the side of sow crate with no heat lamp and 0.64 m on the side with the heat lamp). Two lengths of farrowing pen were used, 2.04 m or 2.20 m. Resulting total floor spaces were 3.10 and 3.34 m 2 for the two pen lengths, respectively, on the Standard treatment and 3.43 and 3.70 m 2 for the two pen lengths, respectively, on the Increased treatment. A replicate consisted of 2 sows with similar parity. Blocking factors were farrowing room and farrowing pen length. The study involved 1, 616 sows in 808 replicates. Management of sows and litters was in accordance with standard commercial procedures. Piglets were weaned at 21 ± 2 days. Data were analyzed using PROC MIXED of SAS (SAS Inst. Inc., Cary, NC); the model included the fixed effects of treatment and the random effects of block and replicate. The number of piglets born alive, dead, mummified, total born, and after cross-fostering were similar ( P > 0.05) for the two pen widths. There was no effect ( P > 0.05) of increasing pen width on either number of piglets weaned (10.9 and 11.0 piglets/sow for Standard vs. Increased, respectively, SEM = 0.11), or pre-weaning mortality (15.2% and 14.6%, respectively). The Increased treatment had greater ( P < 0.05) litter birth weight (20.2 kg vs. 19.7 kg for the Standard treatment, SEM = 0.18) and weaning weight (74.5 kg vs. 72.8 kg for the Standard treatment, SEM = 0.65). However, there was no effect ( P > 0.05) of treatment on average piglet birth or weaning weight. There were no differences ( P > 0.05) between treatments for the causes of piglet mortality. There were no commercially important effects of the larger farrowing pen width on litter performance. Further research is needed to validate the results of this study and to determine the effects of farrowing pen width and design as litter sizes continue to increase.